The Role of Personalized Exercise Protocols Informed by Gut Microbiome Analysis in Improving Metabolic Syndrome Outcomes: A Randomized Controlled Trial - A. AL-Elaimat, Mo'tasem; Z. Alkhawaldeh, Tamara; A. Kadoumi, Obada; H. Alsnayan, Balqis; A. Khalil, Leen; S. Alziadat, Momen; M. Afify, Amira; M. Elgohary, Ola; S. Khalil, Shaymaa; M. Ghorab, Hisham; et al. (Journal of Neonatal Surgery, 2025)
Metabolic syndrome (MetS) is increasingly becoming a global health concern. It is defined by obesity, insulin resistance, high blood pressure, and high triglyceride levels (Saklayen, 2018). Regarding the microbial community, recent discoveries have shown that the gut can influence the metabolic status. However, there is still an open question of how one should design the exercise program with the gut microbiota profiling information. This research seeks to establish the impact of a customized exercise program on metabolic syndrome based on the subjects' gut microbiome. The study employed a randomized controlled trial (RCT) design whereby ten participants diagnosed with MetS underwent gut microbiome assessment via 16S rRNA gene sequencing, a polymerase chain reaction (PCR)-based method that identifies microbial diversity and composition (Dugas, et al., 2018). They were given specific exercises that would directly address their excess of gut microbiota and abnormal metabolic profiles. To evaluate the efficacy of these individualized interventions at various periods up to the twelfth week, biochemical parameters with implications in a clinical context, including fasting blood glucose, lipid profile, Body Mass Index (BMI), and biomarkers of inflammation, were quantified in the study. This metabolic improvement in the patients was most significant for those who had taken a microbiome-based exercise intervention compared to those on regular exercise. There were enhancements in the capacity that bodies had to respond to insulin, BMI, and lipid profile. Moreover, the alteration of the microbial structure was also seen to be positive, indicating enhanced richness. Further research should also be carried out to establish the time effectiveness of such approaches and ensure that other people can use them.